2013
DOI: 10.1021/bi400590h
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpy–Entropy Compensation in Biomolecular Halogen Bonds Measured in DNA Junctions

Abstract: Interest in noncovalent interactions involving halogens, particularly halogen bonds (X-bonds), has grown dramatically in the past decade, propelled by the use of X-bonding in molecular engineering and drug design. However, it is clear that a complete analysis of the structure-energy relationship must be established in biological systems to fully exploit X-bonds for biomolecular engineering. We present here the first comprehensive experimental study to correlate geometries with their stabilizing potentials for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(97 citation statements)
references
References 58 publications
4
93
0
Order By: Relevance
“…This desolvation process was endothermic, so the absolute H values for the second eluted enantiomer of HBipy 29 was lower than that for the first eluted enantiomer. Moreover, if we compare the enthalpy/entropy contributions to retention of 29 to those of the other extreme of the series, namely HBipy 5, we observe that despite both compounds contain iodine and bromine as substituents, in the first case the hindrance generated by the presence of four iodine atoms in close proximity increases the interaction with the CSP and reduces the rotational degree of freedom of the compound ((M)- In this regard, it is interesting to note that, as pointed out by Carter and co-workers [56], despite halogen bonds involving iodine atoms are enthalpically favoured over those involving smaller halogen atoms, this situation may be more than compensated by an entropic penalty due to a crowding effect, resulting in optimal stabilization by a Br· · ·O instead of an I· · ·O interaction. Moreover, it is reported that, in the gas phase, '-hole' interactions with neutral bases are often thermodynamically unfavourable due to the relatively large entropy loss upon complex formation [2].…”
Section: Thermodynamic Aspects Of Enantioseparationssupporting
confidence: 57%
“…This desolvation process was endothermic, so the absolute H values for the second eluted enantiomer of HBipy 29 was lower than that for the first eluted enantiomer. Moreover, if we compare the enthalpy/entropy contributions to retention of 29 to those of the other extreme of the series, namely HBipy 5, we observe that despite both compounds contain iodine and bromine as substituents, in the first case the hindrance generated by the presence of four iodine atoms in close proximity increases the interaction with the CSP and reduces the rotational degree of freedom of the compound ((M)- In this regard, it is interesting to note that, as pointed out by Carter and co-workers [56], despite halogen bonds involving iodine atoms are enthalpically favoured over those involving smaller halogen atoms, this situation may be more than compensated by an entropic penalty due to a crowding effect, resulting in optimal stabilization by a Br· · ·O instead of an I· · ·O interaction. Moreover, it is reported that, in the gas phase, '-hole' interactions with neutral bases are often thermodynamically unfavourable due to the relatively large entropy loss upon complex formation [2].…”
Section: Thermodynamic Aspects Of Enantioseparationssupporting
confidence: 57%
“…Using this system, we have shown that the strength of halogen bonds increases according to the series F < Cl < Br < I, with energies ranging from −0.52 to −6 kcal/mol 17 . In addition, as the X-bonding energy becomes more negative and stabilizing, the geometry becomes more ideal (the Σ R vdW becomes shorter relative to the standard atomic radii and the approach of the acceptor, Θ 1 , becomes more linear towards the σ-hole) 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The system competes a BXB against analogous H-bonds to stabilize a four-stranded DNA junction 15 and, with the energy of the H-bond now determined, the actual energy of each BXB geometry can be determined in isolation 17, 40 . Using this system, we have shown that the strength of halogen bonds increases according to the series F < Cl < Br < I, with energies ranging from −0.52 to −6 kcal/mol 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Our models also explain the favorable effect of a meta-fluorine atom on the binding affinity of ligands with more polarizable iodine atoms interacting with this site, and suggest the existence of an additional secondary halogen bond in the S2 site. As pointed out by Carter et al [37], although halogen bonds involving iodine are enthalpically favored over those involving smaller halogen atoms, this situation may be more than compensated by an entropic penalty due to crowding effects in their DNA model, resulting in optimal stabilization by a BrÁÁÁO instead of an IÁÁÁO interaction. This does not seem to be our case where iodine, as shown experimentally [12], leads to the highest enzyme inhibitory potencies and, in the present study, to the (relatively) shortest XÁÁÁO distances and most favorable C-XÁÁÁO and XÁÁÁO=C angles.…”
Section: Discussionmentioning
confidence: 97%